Strategic Thinking of Ayatollah Khomeini in the Iranian Islamic Revolution - Prihandono Wibowo (Future Science, 2022)
The Iranian Islamic Revolution is one of the most critical events in the study of international relations. This revolution overthrew the ruling regime and gave rise to the Islamic Republic of Iran as a country that applies Islamic teachings as the basis of the state. The Iranian Islamic Revolution also signaled the relevance of the role of Islamic movements in socio-political movements. In addition, the Islamic Revolution of Iran also signifies the trend of desecularization that has characterized international relations for decades. The Islamic Republic of Iran has survived more than four decades despite external pressures. Ayatollah Khomeini was a critical actor in the Islamic Revolution of Iran. Ayatollah Khomeini's thoughts inspired the Iranian people to resist the regime's oppression. Ayatollah Khomeini's thoughts also inspired the Iranian people to accept the form of Iran as an Islamic state. This paper explores the relationship between Ayatollah Khomeini's strategic thinking and the Iranian Islamic Revolution. The method used in this research is qualitative by analyzing Ayatollah Khomeini's statements on religion and revolution.